Comparison of the Value of Welfare Principles in National Law and Islamic Law - Paris Manalu; Sugianto Sugianto; Andi Lala (International Journal of Social Service and Research, 2023)
The welfare state not only encompasses the organization of welfare or social services but emphasizes that everyone is entitled to social services as their right. The polarization of the goals of the welfare state is formulated to establish indicators as tools for assessing whether society is prosperous or not. Speaking of the concept of the rule of law, Islam as a perfect religion also has a concept of statehood. The methodological approach in this research is normative legal research (normative juridical). The type of research used is descriptive research. The data sources obtained by the author are primary legal materials and secondary legal materials. The data collection method used in this research is literature study. The data analysis method used in this research is qualitative method. The results of social welfare that have developed today indicate that there are citizens whose basic needs are not adequately met by the state. As a result, there are still citizens who face obstacles in the implementation of social functions, making it difficult for them to lead a dignified and decent life. Islam is not just a religion that contains a set of ritual doctrines, but Islam is a holistic and systematic worldview. Islam as al-din encompasses all aspects of human life, including statehood and law.